Effect of Combination of Inorganic Fertilizer and Number of Shoots on Early Growth of Sugar Cane (Saccaharum Officinarum L) - Suwanan Suwanan; A Miftakhurrohmat A Miftakhurrohmat (Nabatia, 2014)
First factor was combination of anorganic fertilizer, consists of four levels ie K1 (Urea 100% with fertilizer ponska 0%) = 1304.378 kg urea/ha, K2 (Urea 75% fertilizer ponska 25%) = 978.2835 kg urea/ha with Phonska 1000 kg/ha, K3 (urea 50% fertilizer ponska 5%) = 652 196 kg urea/ha with Phonska 2000 kg/ha, K4 (urea 25% fertilizer Phonska 75%) = 326.0945 kg urea/ha with Phonska 3000 kg/ha and K5 (Urea 0% with fertilizer ponska 100%) = Phonska 4000 kg/ha, while the second factor is the number of buds, comprising two kinds, namely T1 (the buds) and T2 (two buds). The data showed that was interaction between combination treatment of anorganic fertilizer and amount of buds at variable leaf area. The best treatment is a combination of Urea 50% fertilizer ponska 5% (Urea 652 196 kg/ha with Phonska 2000 kg/ha) and number of buds one (T1K3) to produce an average of leaf widest (14:50 cm2) age 30hst, and treatment inorganic fertilizer effect on the variable leaf area, root length (59.54cm) and the weight of the root (9.072gr), treatment K3 (urea 50% fertilizer ponska 5%) = 652 196 kg urea/ha with Phonska 2000kg/ha effect on the variable area leaf, as well as observation of a variable length of root and root weight occurred in treatments K5 (urea fertilizer Phonska 0% to 100%) = urea 0 g/ha Phonska 4000 kg/ha. Treatment buds number one (T1)was siginificantly different on observed variabel of plant diamater and “luas daun” has good effect.